Why is intravenous chemotherapy cancelled and how often. Could it be prevented? A prospective analysis of all planned and given intravenous anti-tumor treatments at the Department of Oncology, Karolinska University Hospital, Stockholm during one month. (July 2015) - Fuentes, Stina; Frödin, Jan-Erik
Abstract Background. Chemotherapy and targeted drugs are important tools in the treatment of malignant diseases. A number of the planned treatments are cancelled late which is a great challenge for the clinic to minimize in order to prevent the risk for misused resources. The aim of this study was to analyze the frequency and reasons for late (<48 hours) cancellations and also to get an overview of all intravenous medical anti-cancer treatment at the clinic. Material and methods. During four weeks in October 2010 all patients with intravenously administered chemotherapy and/or targeted drugs were registered at the Department of Oncology, Karolinska University Hospital. The survey comprehends the vast majority of all such treatment for solid tumors in adult patients in the Stockholm region with two million inhabitants. All bookings and late cancellations including their reasons were recorded. Diagnoses, treatment indication, line of treatment and survival, in particular short term survival, were analyzed. Results. Almost 3000 bookings for 1460 patients were included and 13% were cancelled late. Patient detoriation was the dominating cause for late cancellation in patients with palliative treatment (59%), while hematological toxicity was most common in the adjuvant group (42%). The most common treatment indication was palliative (62%). Of the palliative treatments, 95% where given in the first to third treatment line. Breast cancer (31.9%) and colorectal cancer (29.9%) were the two most common diagnoses. Seventy-one patients (4.9%) died within two months after the treatment. Conclusion. A more careful selection and monitoring of the patients might reduce the number of late cancellations due to patient detoriation. To record performance status (PS) as a routine for all patients might be helpful in that process. If the number of late cancellations could be reduced, resources at the clinic could be used more efficiently.